Experimental Demonstration of FTN-NRZ, PAM-4, and Duobinary Based on 10-Gbps Optics in 100G-EPON - Hong-Bo Zhang; Ning Jiang; Zhi Zheng; Wen-Qin Wang (IEEE Photonics Journal)
This paper presents an experimental demonstration of 100-Gbps time- and wavelength-division multiplexed passive optical network (TWDM-PON) with 4 $ \;×$ 25-Gbps downstream transmission. We take a comparison of faster-than-Nyquist nonreturn-to-zero (FTN-NRZ), four-level pulse amplitude modulation (PAM-4), electrical duobinary (EDB), and optical duobinary (ODB) on the same transmission link. The use of low-cost 10-Gbps optics in combination with digital signal processing (DSP) makes it feasible for a 25-Gb/s per wavelength transmission over 20-km standard single-mode fiber (SSMF) in a cost-effective way. The spectra efficiency and ISI robustness by going to the higher rate are analyzed theoretically. We achieve link budgets of 33.18 dB for FTN-NRZ, and less than 30 dB budgets for PAM-4, ODB, and EDB in downstream transmission. FTN combination with feedforward equalization (FFE) allows FTN-NRZ to have a 4.18 dB margin in power requirement of PR(x) 30 of 10G-EPON, whereas PAM-4 and ODB with FFE also meet PR(x) 30 with 0.25 dB margin. The results indicate that FTN-NRZ, PAM-4, and ODB can be used for 100G-EPON with 10-Gbps optics, and FTN-NRZ has better performance than other modulations, which is more suitable for next-generation 100G-EPON transmission technique with low cost.